2022
DOI: 10.3390/ph15091147
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast and Acute Coronary Syndrome: The Endowed Drug

Abstract: Acute coronary syndrome (ACS) is a set of signs and symptoms caused by a reduction of coronary blood flow with subsequent myocardial ischemia. ACS is associated with activation of the leukotriene (LT) pathway with subsequent releases of various LTs, including LTB4, LTC4, and LTD4, which cause inflammatory changes and induction of immunothrombosis. LTs through cysteine leukotriene (CysLT) induce activation of platelets and clotting factors with succeeding coronary thrombosis. CysLT receptor (CysLTR) antagonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 112 publications
2
25
0
Order By: Relevance
“…Dumont et al found that CoQ10 had a potential effect on the reduction of βA pathology and improve cognition in the transgenic mice model of AD [ 70 ]. Thus, treatment with CoQ10 could be effective in the management of AD by reducing oxidative stress and inflammatory changes [ 71 , 72 , 73 ].…”
Section: Statins and Admentioning
confidence: 99%
“…Dumont et al found that CoQ10 had a potential effect on the reduction of βA pathology and improve cognition in the transgenic mice model of AD [ 70 ]. Thus, treatment with CoQ10 could be effective in the management of AD by reducing oxidative stress and inflammatory changes [ 71 , 72 , 73 ].…”
Section: Statins and Admentioning
confidence: 99%
“…In addition, among Indian cancer patients with inadequate or deficient blood levels of vitamin D, an increase in VDR expression was seen in 110 cases of oral neoplasms, premalignant nodules, and oral cancer [ 21 ]. In addition, ACS pathophysiology includes the activation of inflammatory pathways, such as the leukotriene pathway, with subsequent reduction in several anti-inflammatory mediators, such as vaspin, and releases of multiple proinflammatory mediators that cause inflammatory changes and induce thrombosis via stimulation of platelets and coagulation factors, resulting in subsequent cardiac thrombosis [ 22 , 23 ]. Thus, maintain VDR gene expression by supplementation of ACS patients with vitamin D may be considered crucial for optimal management due to its anti-inflammatory and antiplatelets effects [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19-induced arrhythmia may increase the risk of ACS through the induction of mismatching between oxygen demand and requirement. 93 The most common arrhythmia related to SARS-CoV-2 infection is sinus tachycardia, with palpitations as the principal clinical presentation. 94 Notably, heart rate in infection is simply a marker of a severe clinical condition and a high systemic response to sepsis at presentation.…”
Section: Arrhythmiamentioning
confidence: 99%